2023
DOI: 10.1002/acm2.14139
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and specificity of secondary dose calculation for head and neck treatment plans

Sonja Wegener,
Ruaa Abu Rashed,
Otto A. Sauer
et al.

Abstract: PurposeSecondary dose calculation (SDC) with an independent algorithm is one option to perform plan‐specific quality assurance (QA). While measurement‐based QA can potentially detect errors in plan delivery, the dose values are typically only compared to calculations on homogeneous phantom geometries instead of patient CT data. We analyzed the sensitivity and specificity of an SDC software by purposely introducing different errors and determined thresholds for optimal decisions.MethodsThirty head and neck VMAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Several present studies have been reported that combining various QA tools improves the sensitivity of error detection 20,34,35 . O'Daniel et al.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Several present studies have been reported that combining various QA tools improves the sensitivity of error detection 20,34,35 . O'Daniel et al.…”
Section: Discussionmentioning
confidence: 92%
“…Several present studies have been reported that combining various QA tools improves the sensitivity of error detection. 20,34,35 O'Daniel et al assessed the effective risk reduction of combinations of QA methods for IMRT/VMAT treatments. 34 They showed that the MC-based secondary dose calculation was available to reduce the overall risk.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations